Taylor Rule’s accuracy in determining the countries short-term nominal interest rate - Wisnu Wibowo, Achmad Fahmi, (Opción, 2020)
The purpose of this study was to observe the difference between the rates determined using the Taylor rule and the rate determined by the monetary authorities of each country. This study used quantitative methods. As a result, the Taylor rule’s accuracy in determining the optimal interest rate is better in countries with inflation conditions that tend to be low and stable. This result implied that the Taylor rule is accurate in determining nominal interest rates in developed countries. In conclusion, as for developing countries, the accuracy of the Taylor rule depends on the country’s inflation situation.